PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI PENDEKATAN KONTEKSTUAL BERBASIS LESSON STUDY UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH DAN HASIL BELAJAR KOGNITIF SISWA SMA - Zainul Mustofa; Herawati Susilo; Mimien Heni Irawati Al Muhdhar (Graduate School of Universitas Negeri Malang, 2016)
Education today, said to be successful if it is able to direct their students are not solely on mastery and understanding of scientific concepts, but also on improving the ability and thinking skills, especially the skills to think critically, meaning that teachers need to teach students to learn to think (teaching of thinking). Results of interviews with subjects biology teacher observation time for thinking abilities, especially the ability to solve problems tenth grade students high school in Malang still in the moderate category and even some are still relatively low. The purpose of this research is to improve the ability to solve the problem of class X students with learning strategies Problem Based Learning (PBL) through a contextual approach based Lesson Study (LS). This type of research is the Classroom Action Research (PTK) by implementing PBL strategies through LS-based contextual approach in an effort to improve problem-solving skills and student learning outcomes. This research was conducted with 2 cycles. The results showed that PBL learning through contextual approach based LS, can enhance problem-solving skills and student learning outcomes, it can be seen from the significant value t test, each of which has a significance value of 0.000 (sig. <0.001). Significance indicate that there are very significant differences between problem-solving skills and student learning outcomes in the first cycle and the second cycle. That is, an increase in problem-solving skills and learning outcomes are very significant from the first cycle to the second cycle. Based on these results, learning by using PBL through contextual approach based LS can be used as input for the teacher to create a creative learning to develop students' thinking skills. Pendidikan dewasa ini, dikatakan berhasil apabila mampu mengarahkan siswanya yang tidak semata-mata pada penguasaan dan pemahaman konsep-konsep ilmiah saja, tetapi juga pada peningkatan kemampuan dan keterampilan berpikir, khususnya keterampilan berpikir tingkat tinggi, artinya guru perlu mengajarkan siswanya untuk belajar berpikir (teaching of thinking). Hasil wawancara dengan guru mata pelajaran biologi saat observasi untuk kemampuan berpikir terutama kemampuan memecahkan masalah siswa kelas X SMA di Kota Malang masih pada kategori sedang bahkan ada juga yang masih tergolong rendah. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan memecahkan masalah siswa kelas X dengan strategi pembelajaran Problem Based Learning (PBL) melalui pendekatan kontekstual berbasis Lesson Study (LS). Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan menerapkan strategi PBL melalui pendekatan kontekstual berbasis LS sebagai usaha untuk meningkatkan kemampuan memecahkan masalah dan hasil belajar siswa. Penelitian ini dilaksanakan dengan 2 siklus. Hasil penelitian menunjukkan bahwa pembelajaran PBL melalui pendekatan kontekstual berbasis LS, dapat meningkatkan kemampuan memecahkan masalah dan hasil belajar siswa, hal ini dapat dilihat dari nilai signifikansi Uji t yang masing-masing memiliki nilai signifikansi 0,000 (sig. <0,01). Berdasarkan hasil tersebut, pembelajaran dengan menggunakan PBL melalui pendekatan kontekstual berbasis LS dapat dijadikan sebagai masukan bagi guru untuk menciptakan pembelajaran yang kreatif untuk dapat mengembangkan kemampuan berpikir siswa.